In Search of the Perfect Thrombosis and Bleeding-Associated Cancer Scale - Wojtukiewicz, Marek Z.; Tesarova, Petra; Karetová, Debora; Windyga, Jerzy (Seminars in Thrombosis and Hemostasis, 2023)
Thrombosis and bleeding are commonly observed in cancer patients, and their management is crucial for positive patient outcomes. A comprehensive, prophylactic, and therapeutic management of venous thrombosis should focus on identifying the patients who would benefit most from treatment to reduce mortality and minimize the risk of thrombosis recurrence without significantly increasing the risk of bleeding. Existing cancer scales provide valuable information for assessing the overall burden of cancer and guiding treatment decisions, but their ability to predict thrombotic and bleeding events remains limited. With increasing knowledge of the pathophysiology of cancer and the availability of advanced anticancer therapies, new risk factors for cancer-associated thrombosis and bleeding are being identified. In this report, we analyze the current literature and identify new risk factors for venous thrombosis and bleeding which are not included in routinely used risk scores. While some existing cancer scales partially capture the risk of thrombosis and bleeding, there is a need for more specific and accurate scales tailored to these complications. The development of such scales could improve risk stratification, aid in treatment selection, and enhance patient care. Therefore, further research and development of novel cancer scales focused on thrombosis and bleeding are warranted to optimize patient management and outcomes.
Keywords: thrombosis; venous thrombosis; cancer-associated thrombosis; risk factors; risk assessment; bleeding; risk scale; risk score